The Application of Artificial Intelligence Technology in Natural Language Processing and Image Processing and Its Ethical and Social Impact - Ma, Wenxiang (International Journal of Computer Science and Information Technology, 2024)
This article aims to explore the application of artificial intelligence technology in the fields of natural language processing (NLP) and image processing, as well as the ethical and social impact of these technologies. It first provides an overview of artificial intelligence technology, including its development history, technical characteristics, and application areas. It then focuses on NLP-based artificial intelligence technology, analyzing its applications and challenges in language understanding, sentiment analysis, and intelligent dialogue. It also delves into image-based artificial intelligence technology, covering the technical principles and development trends of image recognition, object detection, and image generation. The paper analyzes the ethical and social impact of artificial intelligence technology, discussing issues such as employment transformation, privacy security, and ethical risks that may arise from AI technology. This research aims to comprehensively understand the current development status and future trends of artificial intelligence technology, as well as the social impact of its applications, providing theoretical references and guidance for research and practice in related fields.